2009
DOI: 10.1108/14777830910950658
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the importance of size as determinant for CSR activities

Abstract: Purpose -This paper aims to contribute to the development and understanding of corporate social responsibility (CSR) by discussing two interrelated characteristics of current literature: a tendency in discourses to portray CSR as equal to the societal activities displayed by and demanded from large, multinational firms; and an increasing focus on and description of "small firm CSR" in research. These two characteristics instigate a limited approach to the meaning of CSR and an unjust dichotomization of CSR bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 50 publications
1
77
1
4
Order By: Relevance
“…The third hypothesis testing this study did not find support for previous studies conducted Robert (1992) and Blombäck and Wigren (2009) who found that age is an important factor that into the company's CSR disclosure determination. In this study, statistical results showed regression coefficient 0.004, t-statistics 2.047 with 0.042 significance.…”
Section: Determination Testing Of Csrcontrasting
confidence: 53%
See 3 more Smart Citations
“…The third hypothesis testing this study did not find support for previous studies conducted Robert (1992) and Blombäck and Wigren (2009) who found that age is an important factor that into the company's CSR disclosure determination. In this study, statistical results showed regression coefficient 0.004, t-statistics 2.047 with 0.042 significance.…”
Section: Determination Testing Of Csrcontrasting
confidence: 53%
“…Study Blombäck and Wigren (2009) explain that company size is an important factor in doing CSR. This study use size of the company (proxied by lnTotal Asset) as determinant of CSR.…”
Section: Firm Sizementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a study of Baumann-Pauly et al (2013) shows that inner characteristics of SMEs facilitate the integration of CSR in business practices, while some characteristics of large corporations influence the communication and reporting of these activities. Nevertheless, size of the company in itself is not necessary a predictor of the CSR behavior, many other factors might be considered to better understand this phenomenon: corporate governance and owner structure; charismatic individuals or leaders; delegation of (financial) decision-making; type of market offer/visibility; place in value chain, closeness to end-user; existence of industry practices and culture; financial resources; relative size of business/unit on location; social embeddedness of business unit (Blombäck & Wigren, 2009). …”
Section: Are Smes Responsible In Different Ways Compared To Corporatimentioning
confidence: 99%